Disability Affordances and Systematic Theology - Powell, Lisa D. (Evangelische Theologie, 2026)
A number of systematic theologians draw from the concept of affordances from design theory and ecological theory to evaluate the way doctrines, theological forms, and method provide either creative opportunities or noxious hindrances to the flourishing of the one encountering the theology. This article introduces the concept of disability affordance to the discussion as a way to consider the dynamic possibility of the affordance for theological construction hospitable to a range of embodiments and life experience. The article concludes with examples from disability theology to illustrate how affordance and disaffordance have functioned within the discipline.